Zika Virus Inhibits IFN-α Response by Human Plasmacytoid Dendritic Cells and Induces NS1-Dependent Triggering of CD303 (BDCA-2) Signaling - Bos, Sandra; Poirier-Beaudouin, Béatrice; Seffer, Valérie; Manich, Maria; Mardi, Cartini; Desprès, Philippe; Gadea, Gilles; Gougeon, Marie-Lise (Frontiers in Immunology, 2020)
Zika virus (ZIKV) dramatically emerged in French Polynesia and subsequently in the Americas where it has been associated with severe neurological complications in adults and newborns, respectively. Although plasmacytoid dendritic cells (pDCs) are a key sensor of viral infection and are critical for initiating an antiviral response, little is known about the impact of ZIKV infection on pDCs. Here, we investigated the susceptibility of human pDCs to infection with multiple strains of ZIKV and further investigated the impact of infection on pDCs functions. We observed that pDCs were refractory to cell-free ZIKV virions but were effectively infected when co-cultured with ZIKV-infected cells. However, exposure of pDCs to ZIKV-infected cells resulted in limited maturation/activation with significant down regulation of CD303 expression, a severe impairment of inflammatory cytokine production, and an inability to mount an IFN- response. We show that ZIKV developed a strategy to inhibit the IFN- response in primary human pDCs likely mediated through NS1-dependent CD303 signaling, thus suggesting a new mechanism of immune evasion.